PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, DAN CAPITAL INTENSITY, TERHADAP PENGHINDARAN PAJAK PADA MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2023-2024 - Novianti Wahida; Wiwin Wiwin (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
In managing a company's tax burden, there are several actions that can be taken, one of which is commonly implemented by companies—tax avoidance. This study aims to analyze the influence of profitability, firm size, and capital intensity on tax avoidance. The research includes two variables: independent and dependent variables. The dependent variable is tax avoidance, which is measured using the Cash Effective Tax Rate (CETR) proxy. Meanwhile, the independent variables in this study are profitability, measured by Return on Assets (ROA); capital intensity, measured by the Capital Intensity Ratio (CIR); and firm size, which is measured using the natural logarithm of total assets. This study adopts a quantitative approach and uses purposive sampling to obtain the sample. The sample consists of 20 companies over a two-year period, resulting in a total of 40 data observations from companies listed on the Indonesia Stock Exchange (IDX) for the years 2023–2024. The analytical technique employed in this research is multiple linear regression, and the data is processed using SPSS software version 22. The results of the study indicate that profitability, capital intensity, and firm size have a significant influence on tax avoidance.